A Trust Framework Utilization in Cloud Computing Environment Based on Multi-criteria Decision-Making Methods. (13th January 2021) - Trabay, Doaa Wagdy; El-Henawy, Ibrahim; Gharibi, Wajeb
Abstract: Cloud computing (CC) is a complete online system of specialized technical resources for data computing and storage management. Many organizations, including small and start-ups, have recommended using CC technology rather than building their own high-costed data centers. Due to the diversity of cloud service providers, identifying appropriate cloud services that can meet users' and organizations' requirements, including trust, is a major challenge. In this paper, we propose a trust framework utilization to evaluate cloud services trust using multi-criteria decision-making and fuzzy logic techniques from different perspectives based on performance, agility, finance, security and usability criteria. The comparison of obtained results with related ones shows that ours are efficient and promising decisions for cloud users and organizations as well.